An analysis of water use trends towards conservation and efficiency in UP Diliman - Tanada, Jose Maria Rafael K. (College of Engineering, University of the Philippines Diliman, 2016)
Adequate water supply is an indicator of the quality of life of Filipinos. Water management plans are effective in reducing costs of educational institutions with large populations. A comprehensive analysis of water consumption of UP Diliman is imperative as initial step to identify areas of improvement with high return on investment so as to avoid waste of money. Such areas identified may range from needing large-scale renovations and investment to needing small-scale changes in personal consumptive habits and administrating practices. This study takes into consideration external factors using PEST analysis that may affect decision-making and the formulation of best practices for water use towards conservation and efficiency in the university. The factors in this study are qualitatively analysed and interpreted through graphs and loading plots from linear regression and factorial analysis.